Prove that:

P(A n B^c) = P(A U B) - P(B)

and

P(A n B^c) = P(A) - P(A n B)

Similar Questions
  1. HII WOULD LIKE TO KNOW WHAT I CAN POSSIBLY PROVE ABOUT EITHER THE BERMUDA TRIANGLE OR ATLANTIS THE LOST EMPIRE WE AARE SUPPOSED
    1. answers icon 4 answers
    1. answers icon 0 answers
  2. uestion 1Video Player A) What theorem can be used to prove that the triangles are congruent? (1 point) Responses SSS SSS ASA ASA
    1. answers icon 1 answer
  3. 7. Prove that tan B� sin B� + cos �B = sec B�.11. Prove that tanλ cos^2λ +sin^2λ/sinλ = cos λ� + sin λ�. 12. Prove that
    1. answers icon 1 answer
more similar questions